The The Effect of Financial Literacy on Investment Decision with Motivation as an Intervening Variable - Moh. Helmi Hidayat; Nur Hidayah Selviyanti (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Objective: This study aims to determine the effect of financial literacy on student investment decisions with motivation as the psychological content of students in deciding to invest as an implementation of the campus curriculum, especially in the Faculty of Islamic Economics and Business. Research Design & Methods: a quantitative study with a population of students at the Islamic Faculty of Economics and Business in Madura. Data was collected via google form and offline dissemination by obtaining 168 respondents. Processing primary data using statistical analysis techniques Package for Social Science (SPSS) with multiple regression analysis methods, path analysis and sobel test. Findings: that financial literacy has a positive and significant effect on motivation. Furthermore, financial literacy and motivation indirectly have a positive and significant effect on investment decisions. In addition, the results of this study indicate that motivation is able to mediate financial literacy on investment decisions of Islamic Economics and Business Faculty students in Madura with a significant influence. Implications & Recommendations: : this research is expected to be used as one of the considerations for students in managing finances, by means of which students can have good financial literacy, interest in investment and be motivated to invest. Contribution & Value Added: this research is the first attempt to examine the effect of financial literacy on investment decisions with motivation as a psychological content. The results of this study indicate that motivation is able to mediate financial literacy on the investment decisions of Islamic Economics and Business Faculty students in Madura with a significant influence.